A historical guide to Edgar Allan Poe - Kennedy, J. Gerald (New York : Oxford University Press, 2001)
Contains four critical essays that examine nineteenth-century American author Edgar Allan Poe's works from a historical perspective, and includes biographical and bibliographical essays, and an illustrated chronology.
Includes bibliographical references (p. 209-231) and index.
Wilson's Senior High School.
Adult
Keywords: Poe, Edgar Allan, -- 1809-1849.; Poe, Edgar Allan, -- 1809-1849 -- Criticism and interpretation; Poe, Edgar Allan, -- 1809-1849.; Poe, Edgar Allan, -- 1809-1849 -- Criticism; Literature and society -- United States -- History -- 19th century; American literature -- History and criticism